2020
DOI: 10.3390/cells9122701
|View full text |Cite
|
Sign up to set email alerts
|

Diet Rich in Simple Sugars Promotes Pro-Inflammatory Response via Gut Microbiota Alteration and TLR4 Signaling

Abstract: Diet is a strong modifier of microbiome and mucosal microenvironment in the gut. Recently, components of western-type diets have been associated with metabolic and immune diseases. Here, we studied how high-sugar diet (HSD) consumption influences gut mucosal barrier and immune response under steady state conditions and in a mouse model of acute colitis. We found that HSD significantly increased gut permeability, spleen weight, and neutrophil levels in spleens of healthy mice. Subsequent dextran sodium sulfate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 87 publications
0
29
0
Order By: Relevance
“…Regular consumption of sweet confectionery in the long term is associated with increasing of pro-inflammatory markers such as C-reactive protein (CRP), interleukin 6 (IL-6) or tumor necrosis alpha (TNF alpha) [68]. In animal studies, a high-saccharide diet led to disruption of barrier integrity, greater gut permeability with a subsequent increasing level of pro-inflammatory markers IL-6, TNF alpha [69]. Further, in human studies, the elevated level of IL-6 or C-reactive protein was positively associated with physical inactivity and negatively related to the amount of leisure time dedicated to physical activity in children and adults [70][71][72].…”
Section: Differences In Basic Eating Habits Between Nwo Owandob and Nwno Preschoolers And Their Connection To Physical Fitnessmentioning
confidence: 99%
“…Regular consumption of sweet confectionery in the long term is associated with increasing of pro-inflammatory markers such as C-reactive protein (CRP), interleukin 6 (IL-6) or tumor necrosis alpha (TNF alpha) [68]. In animal studies, a high-saccharide diet led to disruption of barrier integrity, greater gut permeability with a subsequent increasing level of pro-inflammatory markers IL-6, TNF alpha [69]. Further, in human studies, the elevated level of IL-6 or C-reactive protein was positively associated with physical inactivity and negatively related to the amount of leisure time dedicated to physical activity in children and adults [70][71][72].…”
Section: Differences In Basic Eating Habits Between Nwo Owandob and Nwno Preschoolers And Their Connection To Physical Fitnessmentioning
confidence: 99%
“…However, while the former increases proinflammatory tuning in gut monocytes the latter worsens the gut barrier function. In both cases, however, interactions between diet and microbiota are necessary for this deleterious effects as they fail to appear in germ-free condition or after transfer of the microbiota to naive mice [16,17].…”
Section: Triggers and Drivers Of Dysbiosismentioning
confidence: 99%
“…On the other hand, simple and digestible carbohydrates (e.g., sucrose, fructose, and glucose) are also indicated to modulate microbial diversity. Furthermore, they would impair gut permeability [ 68 , 69 ]. Fajstova et al showed that a diet rich in simple sugars (high-sugar diet or HSD) induced an alteration in gut microbial composition and inflammatory immune responses in mice and that the HDS-fed mice showed increased severity of experimental colitis [ 68 ].…”
Section: Modulation Of the Gut And Oral Microbiome By Glucosementioning
confidence: 99%
“…Furthermore, they would impair gut permeability [ 68 , 69 ]. Fajstova et al showed that a diet rich in simple sugars (high-sugar diet or HSD) induced an alteration in gut microbial composition and inflammatory immune responses in mice and that the HDS-fed mice showed increased severity of experimental colitis [ 68 ]. In the field of autoimmune diseases, it has been reported that dietary free sugar intake was associated with the disease activity of systemic lupus erythematosus (SLE) [ 69 ], which indicates a possible role for sugar intake in SLE and other autoimmune rheumatic diseases.…”
Section: Modulation Of the Gut And Oral Microbiome By Glucosementioning
confidence: 99%